2005
DOI: 10.1002/app.22080
|View full text |Cite
|
Sign up to set email alerts
|

Application of polymer gels containing side‐chain phosphate groups to drug‐delivery contact lenses

Abstract: Hydrogels that contain phosphate groups in side chains were studied for their usefulness in drug-delivery soft contact lenses (SCLs). Naphazoline, a model drug having a cationic group, was incorporated into an SCL because of its phosphate groups and was released over a period of about 14 h. For the SCL, the naphazoline content was equivalent to the phosphate group content. It is suggested that drug-delivery SCLs can be designed to contain the needed amount of a drug through the choice of the ionic group for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
45
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(46 citation statements)
references
References 49 publications
1
45
0
Order By: Relevance
“…Soft contact lens-based DDSs have been investigated by several approaches: (1) Soak and absorption of drug solution [86]; (2) piggyback contact lens combined with a drug plate or drug solution [87]; (3) surface-modification to immobilize drugs on the surface of contact lenses [88]; (4) incorporation of drugs in a colloidal structure dispersed in the lens [89]; (5) ion ligand-containing polymeric hydrogel [90]; and (6) molecularly imprinting of drugs [91,92].…”
Section: Contact Lensmentioning
confidence: 99%
“…Soft contact lens-based DDSs have been investigated by several approaches: (1) Soak and absorption of drug solution [86]; (2) piggyback contact lens combined with a drug plate or drug solution [87]; (3) surface-modification to immobilize drugs on the surface of contact lenses [88]; (4) incorporation of drugs in a colloidal structure dispersed in the lens [89]; (5) ion ligand-containing polymeric hydrogel [90]; and (6) molecularly imprinting of drugs [91,92].…”
Section: Contact Lensmentioning
confidence: 99%
“…[17][18][19] In previous studies, a drug delivery hydrogel material consisting of 2-hydroxyethyl methacrylate (HEMA) was used as the main material, ethyleneglycole dimethacrylate (EGDMA) as a crosslinking agent, methacrylamide (MAm) as a functional group, and methacrylic acid or phosphoric acid as an anionic material group. 17,18 The polymer-drug interaction between phosphoric acid as an anionic material, and naphazoline as a cationic drug 19 was also studied, and it was found that HEMA, EGDMA, and MAm were required, since both cationic and anionic monomers are essential to a synthesized drug delivery hydrogel SCL. The reason for this is that the hydrogel material is not able to maintain the strength and the shape necessary for an SCL if either a cationic or anionic monomer was not included.…”
mentioning
confidence: 99%
“…[11][12][13] For instance, the hydrogels containing the comonomers methacrylic acid (MAA) or NVP (N-vinyl pyrrolidone) has been shown to be capable for a large amount of water. [14][15][16][17] The HEMA that has been copolymerized with anionic monomers such as MAA to introduce charged moieties in the polymeric network was found to improve the biological performance of the material. 10,18 For that reason, HEMA-MAA hydrogels are often used for soft hydrogel contact lens.…”
Section: Introductionmentioning
confidence: 99%